Frequency Measurement of Dynamic Stress in Polarization Maintaining Fibers - Hongxia Zhang; Yuyao Wang; Guoqiang Wen; Dagong Jia; Tiegen Liu (IEEE Photonics Journal)
Up to now, the distributed polarization coupling (DPC) measurement system based on white light interferometry (WLI) has been mainly studied for static and quasi-static measurement. In this paper, we developed the DPC system to measure the instantaneous frequency of dynamic stress. First, we set up a model of transversal stress on the panda polarization maintaining fiber (PMF) and simulated the interferograms of dynamic coupling points when the PMF is subjected to stress of cosine wave, sawtooth wave and square wave. Then, we did groups of experiments to measure the interferograms of dynamic coupling points, including cosinoidal coupling point, sawtooth wave coupling point, square wave coupling point, and two cosinoidal coupling points. By applying wavelet transform to the envelops of interferograms, we can obtain the time-frequency distribution images and demodulate the instantaneous frequency of external stress. The absolute error of experiments is less than 1.84 Hz. Finally, we deduced the upper and lower limits for frequency measurement and discussed the methods of enlarging the frequency range in detail. The method introduced in this paper has potential application in fiber sensing of dynamic stress.